Jovens e escola justa: o cotidiano nos cursos técnicos integrados ao Ensino Médio (IFRS Campus Caxias do Sul/ RS) - Pires, Jocianne Giacomuzzi (My University, 2019)
This dissertation had as object of study the everyday life of the youth in the Technical Courses Integrated to High School, at IFRS Campus Caxias do Sul and the realization of the right to the education, starting from the concept of fair school, proposed by Fraçois Dubet. The main objective of this research consists on analyze juvenile trajectories who exists on Technician Courses Integrated to the High School bonded to the right of education from the perspective of a fair school. The mapping of different youth trajectories was sought to identify how young people experience the realization of the right to education and how the relations between their youth trajectories and the realization of the right to education are established. The theoretical basis for this study starts from contributions of authors such as Pais (1999; 2001; 2002; 2003), Stecanela (2002; 2009; 2010; 2013; 2016; 2018), Dayrell (2001; 2002; 2003; 2007; 2014), Carrano (2000; 2002; 2003; 2014), Sposito (1996; 2014; 2018), Silva (2013; 2015); Cury (2002; 2011), Dias (2007), Dubet (2001; 2003; 2004; 2008), Valle (2013), Schilling (2013; 2016) and others. The methodological anchor was based on sociology of everyday life, from Pais (2002) using the map Emic-Ritmico, a graphical tool where young people describe their life and the school life. From the maps, the juvenile narratives appeared, which were analyzed by the Discursive Textual Analysis of Moraes and Galiazzi (2007; 2011). From the process of deciphering the narratives, came five main thematic categories: The entry into the Integrated Technician to High School - A process of readjustment of the ways of being a student; Entering the competition- The rules of the game; Centrality of the school and the absence of "do nothing time"; Sociability and interpersonal relationships; and Possibilities of significance of the juvenile condition in the school. The results of the research showed that there are mechanisms that can be considered unfair in the everyday life of the Technician Courses Integrated to the High School. Among them, the most outstanding are the individual performances legitimized by the students, culminating in adequacy and readjustment of the ways of being a student and the limitation of the "do nothing time”, in order to adapt to the meritocratic school culture. However, there are many aspects that bring the institution closer to a fair school, such as access to assets and the world of work and the development of the capacity to dominate one's own lives. In addition, students demonstrate how the institution's potential is socio-cultural diversity, the sociabilities developed from the school, the quality of education and the dialogical relations they establish. Even if young people from the Technical Courses Integrated to High School of the IFRS Campus Caxias do Sul talk about the idea of youth as a passage, there is evidence of a youth who wants to "be more" (FREIRE, 1996). They need space for the development of its autonomy, assuming a critical and autonomous position in front of itself and in front of its reality. The juvenile narratives indicate the demand for a more humanized school, which encourages reflection through dialogue.
presente dissertação teve como objeto de estudo as trajetórias que compõem o cotidiano dos jovens nos cursos Técnico Integrados ao Ensino Médio, do IFRS Campus Caxias do Sul e a efetivação do direito à educação, partindo do conceito de escola justa, proposto por François Dubet. O objetivo principal da pesquisa consistiu em analisar trajetórias juvenis presentes no contexto dos cursos Técnicos Integrados ao Ensino Médio, em articulação com a efetivação do direito à educação, na perspectiva de uma escola justa. Para isso, buscou-se o mapeamento de diferentes trajetórias juvenis, a fim de identificar como os jovens vivenciam a efetivação do direito à educação e como se estabelecem as relações entre as suas trajetórias juvenis e a efetivação do direito à educação. O referencial teórico tomado como base para o estudo parte das contribuições de autores, como: Pais (1999; 2001; 2002; 2003), Stecanela (2002; 2009; 2010; 2013; 2016; 2018), Dayrell (2001; 2002; 2003; 2007; 2014), Carrano (2000; 2002; 2003; 2014), Sposito (1996; 2014; 2018), Silva (2013; 2015); Cury (2002; 2011), Dias (2007), Dubet (2001; 2003; 2004; 2008), Valle (2013), Schilling (2013; 2016), entre outros. A ancoragem metodológica baseou-se na Sociologia do Cotidiano, de Pais (2002), utilizando como instrumento o mapa Emic-Rítmico, um instrumento gráfico no qual os jovens retratam seus percursos de vida e seus percursos escolares. A partir dos mapas, emergiram as narrativas juvenis que foram analisadas pela Análise Textual Discursiva de Moraes e Galiazzi (2007; 2011). Do processo de decifração das narrativas surgiram cinco temáticas principais: O ingresso no Técnico Integrado ao Ensino Médio – Um processo de readequação dos modos de ser estudante; Entrando na competição– As regras do jogo; Centralidade da escola e a ausência do “não fazer nada”; Sociabilidade e relações interpessoais; e Possibilidades de significação da condição juvenil na escola. Os resultados da pesquisa mostraram que há mecanismos que podem ser considerados injustos no cotidiano escolar dos cursos Técnicos Integrados ao Ensino Médio do IFRS Campus Caxias do Sul. Entre eles, destacam-se a valorização dos desempenhos individuais, legitimados pelos estudantes, que culminam na adequação e readequação dos modos de ser estudante, e a limitação do tempo de “não fazer nada”, a fim de se adaptarem à cultura escolar meritocrática. Entretanto, há vários aspectos que aproximam a instituição a uma escola justa, como o acesso aos bens e ao mundo do trabalho e o desenvolvimento da capacidade de dominar as próprias vidas. Ademais, os estudantes demonstram, como potencialidades da instituição, a diversidade sociocultural, as sociabilidades desenvolvidas a partir da escola, a qualidade da educação e as relações dialógicas que estabelecem. Assim, mesmo que os jovens dos cursos Técnicos Integrados ao Ensino Médio, do IFRS Campus Caxias do Sul, discorram sobre a ideia da juventude como passagem, há indícios de uma juventude que deseja “ser mais” (FREIRE, 1996), que necessita de espaços para o desenvolvimento de sua autonomia, assumindo uma postura crítica e autônoma frente a si e frente a sua realidade. Assim, as narrativas dos jovens indicam a demanda por uma escola mais humanizada, potencializadora da reflexão por meio do diálogo.
Keywords: Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (Campus Caxias do Sul); Ensino técnico; Ensino integrado; Ensino médio; Ensino superior; Technical education; Articulation (Education); High school; College teaching